2022
DOI: 10.3390/ijerph19020677
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Circular Economy Transition in Organizations: A Moderated Mediation Model

Abstract: The notion of Corporate Environmental Responsibility has been extensively researched in the literature so far, but less is known about how this concept fits into the circular economy paradigm. We performed a moderated mediation analysis in order to identify the mechanism that links corporate environmental responsibility with readiness for change towards a circular economy business model. The findings from 311 respondents show that there is a positive association between corporate environmental responsibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(53 reference statements)
0
5
0
1
Order By: Relevance
“…On the other side, ref. [58] found that corporate environmental responsibility (CER) is positively related to the readiness for moving towards a circular business model. Perceived CE drivers act as mediators, while perceived CE barriers moderate the relationship between CER and readiness for change-acting, reducing the positive effect.…”
Section: Circular Economy: the Transition And The Readiness Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, ref. [58] found that corporate environmental responsibility (CER) is positively related to the readiness for moving towards a circular business model. Perceived CE drivers act as mediators, while perceived CE barriers moderate the relationship between CER and readiness for change-acting, reducing the positive effect.…”
Section: Circular Economy: the Transition And The Readiness Levelmentioning
confidence: 99%
“…Ref. [58] found that corporate environmental responsibility (CER) positively influences the readiness for change in organizations. Parallelly with the activities on the supply side and aimed at increasing the level of companies' readiness for implementing new business model based on CE, different activities should be realized on the demand side in terms of deploying the environmental consciousness of citizens and consumers through the programs of environmental education and similar activities of public authorities and decision-makers, as was emphasized in the research of [66].…”
Section: Conceptualization Phase: Literature Reviewmentioning
confidence: 99%
“…La categoría ecoinnovación y tecnologías representa las formas inter y multidisciplinarias (Weigend et al, 2019) que fomentan la transición desde un sistema productivo agroalimentario lineal hacia los principios de la producción circular y de consumo sostenible (Muscio & Sisto, 2020) bajo el fundamento de procesos gerenciales, y el uso de recursos tecnológicos que incluyen cambios positivos tangibles al ambiente (Tarhini, 2022;Bîrgovan et al, 2022). Otros hallazgos presentan innovaciones organizativas y conocimientos derivados de modelos de negocios agroalimentarios (Lee et al, 2020), que se focalizan en la reducción de la pobreza y las mejoras de los procesos de las organizaciones (Cabrales et al, 2021) y su relación con los stakeholders.…”
Section: Síntesis Y Creación De La Red Semántica: Economía Circularunclassified
“…Despite these efforts, there is no one-size-fits-all circular economy model at this time. Different players have different views of what CE can or should describe [35], and the connection to sustainability is not always obvious [8]. Despite the CE definition's ambiguous constraints, particular procedures are required to track the CE's progress.…”
Section: Circular Cities Indicatorsmentioning
confidence: 99%